Better Land and Nitrogen Complementarity for Green Forage Than for Silage in Barley–Field Bean Intercropping - Francesco Giovanni Salvo Angeletti; Silvia Pampana; Sergio Saia; Marco Mariotti (Agronomy, 2023)
Biomass and nitrogen (N) accumulation in intercrops for forage production under different fertilizations have seldom been assessed and, more occasionally, have been investigated at different stages. The biomass and N contents of barley (Hordeum vulgare L.) and field bean (Vicia faba L. var minor) grown as sole crops and intercrops, with five N rates from 0 to 200 kg ha−1, both at the heading and early dough stage of the cereal, for green forage and silage purposes, were determined in a two-year field experiment in Central Italy. We discovered differences between the two harvests both in their biomass production and N content as, at the latter stage, they, respectively, increased by 27 and 13%. The sole and intercropped crops showed differences at the two stages, essentially in the response of their inflorescences. N fertilization was more effective at the latter stage, because of the barley’s response to the nutrient availability. However, while nitrogen use efficiency improved with crop ageing, the values of the land equivalent ratio and the nitrogen land equivalent ratio declined; thus, a better complementarity in the use of land and N between the two species seemed to be achieved when the intercrop was grown for green forage purposes.